Marketing Public Relations MGT Radio 101.1 FM dalam Menarik Pengiklan - Mahdawanti Dian Bachtiar; Nova Yuliati (UNISBA Press, 2023)
Abstract The development of mass media in Indonesia is quite rapid, especially radio, now radio has become a medium that is very loved by listeners to accompany their time, such as working, studying, or spending spare time. The rapid development in the radio industry makes competition very tight between radio within the city and outside the city. Marketing Public Relations has a very important role at this time, not only about the company's self-image but also about marketing and programs run by the radio company. It has very good listeners so that it can maintain its existence in the radio industry or can be a reference to attract advertisers. With so many radio industries today, the competition is getting tougher. Especially in the world of advertising cooperation, which will support radio companies in the future. The purpose of this study is to find out how the Marketing Public Relations carried out by MGT Radio 101.1 FM in attracting advertisers in the midst of its competition with other radio industry companies, and how to keep advertisers and listeners. In this study using the theory of Three Ways Strategy, Pull, Push, and Pass Strategy. Then this research also uses qualitative descriptive in its method. This research has an object of research, namely MGT Radio 101.1 FM, where the radio is adult and youth radio which is currently being loved by the public. MGT Radio 101.1 FM Bandung has many programs that can be enjoyed by listeners at any time, the program is said to be able to attract advertisers and listeners, as well as many other radio industries have programs to attract listeners and advertisers. The results of this study indicate that: The process of pull strategy (push), push strategy (pull), and pass strategy (expand marketing) is carried out by MGT Radio by implementing good coordination, the way marketing public relations is carried out, and always applying a good image. positive. Abstrak Perkembangan Media Massa di Indonesia cukup pesat khususnya radio, kini radio menjadi media yang sangat digandrungi oleh para pendengar untuk menemani sela-sela waktu mereka seperti bekerja,belajar,atau mengisi waktu luang. Perkembangan yang pesat dalam industry radio membuat persaingan yang sangat ketat antar radio dalam kota maupun luar kota. Marketing Public Relations mempunyai peranan yang sangat penting saat ini, bukan hanya tentang self image perusahaan saja tetapi mengenai marketing dan program yang dijalankan oleh perusahaan radio tersebut mempunyai pendengar yang sangat bagus sehingga dapat mempertahankan eksistensinya dalam industry radio ataupun dapat menjadi acuan untuk menarik para pengiklan. Dengan banyaknya industry radio kini, makin ketat pula persaingannya. Apalagi dalam dunia Kerjasama iklan , yang nantinya akan menunjang perusahaan radio kedepannya. Tujuan dari Penelitian ini adalah untuk mengetahui bagaimana Marketing Public Relations yang dilakukan MGT Radio 101.1 FM dalam menarik pengiklan di tengah-tengah persaingannya dengan perusahaan industry radio yang lainnya, serta bagaimana caranya untuk tetap mempertahankan pengiklan dan para pendengarnya. Dalam penelitian ini menggunakan teory Three Ways Strategy, Pull,Push, dan Pass Strategy. Lalu penelitian ini juga menggunakan deskriptif kualitatif dalam metodenya. Penelitan ini mempunyai objek penelitian yaitu MGT Radio 101.1 FM, yang dimana radio tersebut adalah radio dewasa dan anak muda yang saat ini sedang banyak digandrungi oleh masyarakat. MGT Radio 101.1 FM Bandung mempunyai banyak sekali program yang dapat dinikmati oleh para pendengar di setiap waktunya, program tersebut di sebut dapat menarik para pengiklan dan pendengar, begitupun industry radio yang lain pun banyak mempunyai program untuk menarik para pendengar dan juga para pengiklan. Hasil dari penelitian ini menunjukan bahwa: Proses pull strategy (mendorong),push strategy (menarik), dan pass strategy (memperluas pemasaran) yang dilakukan oleh MGT Radio dengan menerapkan koordinasi yang baik, cara marketing public relations yang dilakukan, dan senantiasa menerapkan citra yang positif.